Prophylactic Altropine administration should be considered during laparoscopic surgery - Maharjan, SK; Tabdar, S (Journal of Kathmandu Medical College, 2014)
Background: Routine use of vagotonic drugs during general anaesthesia with mechanical ventilation and carboperitoneum creation during laparoscopic surgery may lead to severe bradycardia and even asystole, which can be countered by prophylactic use of Atropine sulphate. Objective: To study whether Atropine sulphate administered one minute after endotracheal intubation will be effective in preventing bradycardia induced by vagotonic anaesthetics and carboperitoneum during laparoscopic surgery. Methods: Ninety two patients of American Society of Anaesthesiologist Physical Status I were included in the study. These patients were randomly divided into two groups (Control group and Atropine group) of 46 each by envelope method. Control group received one mL of saline and Atropine group received 0.6 mg (one mL) Atropine one minute after endotracheal intubation. Heart rate, systolic, diastolic and mean arterial pressures were monitored before intubation; one, three and fi ve minutes after intubation; fi ve, 15 and 30 minutes after carboperitoneum creation and before and after extubation. Atropine 0.6 mg was given intravenously if any of patients developed heart rate less than 50 beats per minute. Results: Demographic characteristics were similar in both groups. Thirty percent (14 out of 46) of patients in control group developed bradycardia immediately after carboperitoneum creation and no patients developed bradycardia in atropine group. Haemodynamic parameters after intubation, during intraoperative period and after extubation were similar in both groups. Conclusion: Vagolytic drug (Atropine sulphate) should be considered if vagotonic anaesthetic drugs are used along with carboperitoneum creation during laparoscopic surgery. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10622 Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, Page : 45-50